Spotlight on idarucizumab and its potential for the reversal of anticoagulant effects of dabigatran - Sié P (Dove Medical Press, 2016)
Pierre Sié Hematology Laboratory, Academic Hospital of Toulouse, Hospital Rangueil, Toulouse, France Abstract: Idarucizumab is the first targeted antidote of dabigatran, a direct oral anticoagulant used for prevention and treatment of venous thromboembolism and prevention of stroke in atrial fibrillation. Idarucizumab is a humanized fragment of a monoclonal antibody, which binds dabigatran reversibly with high affinity and, when administered intravenously, immediately neutralizes its anticoagulant effect. It is rapidly cleared by the kidney with captured dabigatran. In Phase I and II trials, no significant adverse events have been reported. Specifically, idarucizumab has no anticoagulant or procoagulant effect by itself. Idarucizumab is currently being evaluated in an ongoing Phase III trial, in patients treated with dabigatran presenting with severe active bleeding or requiring emergency surgery or an invasive procedure and are at high risk of bleeding. The results of the interim analysis confirm the ability of idarucizumab to neutralize dabigatran instantaneously, without rebound effect, except in rare patients with very high baseline levels of anticoagulant. Although not definitely proving clinical efficacy, due to the noncontrolled design of the trial and the heterogeneity of patient conditions, these promising results on an intermediate criterion with strong rationale have led to the approval of idarucizumab for these indications. However, several questions are unresolved. First, activity measurement of dabigatran in blood, useless in current practice, could be useful to guide the treatment and avoid over- or underutilization of the antidote; but so far, it has not been largely available in real time. Second, the translation of anticoagulant neutralization to an effect on mortality and better outcome is highly dependent on the global management of these patients, especially rapid diagnosis, supportive care, and easy access to antidote administration. Although idarucizumab represents a remarkable achievement in drug design and development, whether it will be an important step toward improved safety of patients treated with dabigatran in the real world will have to be demonstrated in the postmarketing phase. Keywords: dabigatran, idarucizumab, bleeding, surgery